KOMPARASI PENERAPAN STRATEGI PEMBELAJARAN MEANS-ENDS ANALYSIS (MEA) DENGAN PROBLEM POSING PADA PEMBELAJARAN MEKANIKA TEKNIK DI SMKN RAJAPOLAH - Indriani, Ine Tri (2017)
StrategipembelajaranMeans-Ends Analysis (MEA) danProblem Posingmerupakanstrategipembelajaran yang dapatmeningkatkankemampuanberpikirkritissiswadalammemecahkansuatumasalah.Penelitianinidilatarbelakangiolehrendahnyahasilbelajarsiswapadamatapelajaranmekanikateknik.Dalampenelitianini, strategipembelajaranMeans-Ends Analysis (MEA) dikomparasikandenganProblem Posingpadapembelajaranmekanikateknik.Strategipembelajaran yang diterapkanpadapenelitianinidiharapkanmampumeningkatkankemampuanpemecahanmasalahmekanikatekniksiswa.Tujuanpenelitianiniuntukmengetahui : (1) gambaranpenerapanstrategiMeans-Ends Analysis (MEA) danstrategiProblem Posingpadapembelajaranmekanikateknik (2) perbedaankemampuanpemecahanmasalahmekanikatekniksiswaantarakelas yang menerapkanstrategiMeans-Ends Analysis (MEA) dengankelas yang menerapkanstrategi Problem Posing.Penelitianinimenggunakandesainpenelitianquasi exsperimentdenganbentukdesainnonequivalent control group design.Sampelpenelitianberjumlah 71 siswakelas X SMKN Rajapolahyaitukelas X TGB 1 sebagaikelas MEA dan X TGB 2 sebagaikelas PP. Instrumenpenelitianterdiridarilembarobservasidantes. Hasilpenelitianmenunjukkanbahwa : (1) strategipembelajaranMeans-Ends Analysis (MEA) danProblem Posing telahditerapkansesuaidengansintak/langkah-langkahdarimasing-masingstrategitersebut; (2) Terdapatperbedaansignifikankemampuanpemecahanmasalahmekanikatekniksiswaantarakelas yang menerapkanstrategiMeans-Ends Analysis (MEA) dengankelas yang menerapkanstrategi Problem Posing. Kata kunci :Means-Ends Analysis (MEA), Problem Posing, MekanikaTeknik;--- Means-Ends Analysis (MEA)learning strategy and Problem Posingis a learning strategy that can improve student's critical thinking skills in solving problem.This research is based on the low learning outcomes of students on the subjects ofTechnique Mechanics. In this research, Means-Ends Analysis (MEA) learning strategy is compared with Problem Posing inTechnique Mechanics.Learning strategy that implemented in this research are expected to improve student'sTechnique Mechanics problem solving skills. The purpose of this research is to know: (1) description of Means-Ends Analysis (MEA) strategy implementation and Problem Posing strategy on Technique Mechanics learning (2) differences in student'sTechnique Mechanics problem solving skills between classes that implement Means-Ends Analysis (MEA) strategy with classes thatimplement the Problem Posing strategy.This research uses quasi exsperiment research design with nonequivalent control group design.The sample of this research is 71 students of class X SMKN Rajapolah that is class X TGB 1 as class of MEA and X TGB 2 as class PP.The research instrument consists of observation sheets and test.The results show that: (1) Means-Ends Analysis (MEA) and Problem Posing learning strategies have been implemented in accordance with the syntax / steps of each strategy; (2) There is a significant difference in student's Technique Mechanics problem solving skills between classes that implement Means-Ends Analysis (MEA) strategy with classes that implement the Problem Posing strategy. Keyword :Means-Ends Analysis (MEA), Problem Posing, Technique Mechanics